Method for producing sintered brown aluminum oxide

By using high alumina bauxite raw ore and alumina to produce sintered brown corundum, the problems of high cost and waste of resources of electromelted brown corundum are solved, and sintered brown corundum with high alumina content, stability and wear resistance are achieved, replacing the use of electromelted brown corundum.

CN119551997APending Publication Date: 2025-03-04新郑市震宇研磨有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411472189.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

In the prior art, electromelted brown corundum has high production costs, low alumina content, uneven components, unstable properties, and wasteful high bauxite resources, making it difficult to replace electromelted brown corundum.

Method used

Using loose structures of high-alumina bauxite raw ore and industrial alumina or calcined alumina powder, sintered brown corundum is produced through steps such as material preparation, material treatment, iron removal, mixing, drying and sintering, which improves the alumina content and adhesion and enhances wear resistance.

Benefits of technology

The sintered brown corundum produced has a high aluminum content and good thermal shock stability. It can replace electromelted brown corundum and exhibits good use effects in many products, improving the strength and wear resistance of brown corundum and extending its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551997A_ABST
    Figure CN119551997A_ABST
Patent Text Reader

Abstract

The invention discloses a method for producing sintered brown aluminum oxide, which comprises the following steps of: crushing bauxite raw ore into particles, mixing the particles with sodium carboxymethyl cellulose and boric acid which are used as binding agents, aluminum oxide and water, grinding into fine particles, treating materials, namely cleaning soil adhered in the transportation process of bauxite, crushing and grinding for later use, crushing and grinding a carbon material for later use, and drying to obtain the sintered brown aluminum oxide. And removing rust outside the scrap iron, crushing and grinding for later use. The sintered brown aluminum oxide is produced by taking high-alumina bauxite raw ore which is loose in structure and cannot be directly sintered and industrial aluminum oxide or calcined aluminum oxide powder as raw materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sintered brown corundum production, and more specifically, to a method for producing sintered brown corundum. Background Art

[0002] At present, the commonly used medium and high-grade aluminum raw materials in the refractory industry mainly include ore calcined materials and electric fused materials. Electric fused materials are produced by electric fusion method. The electricity cost is very high, which is an important reason why the price of electric fused brown corundum has been rising in recent years. The ore calcined materials produced by the ore sintering method with lower cost cannot replace the use requirements of electric fused brown corundum in related products due to low alumina content, uneven composition, and relatively unstable properties. Sintered material processing, alumina is accompanied by clay minerals, which do not adhere to carbon materials and iron filings. Iron filings are oxidized to form rust. After heating, the rust forms black impurities, which affect the quality of sintered brown corundum. Brown corundum made of conventional materials has more impurities and lower adhesion. It is easy to break in the middle, which is not conducive to the service life of brown corundum. The block blank is directly fired, the heat uniformity is low, the sintering completeness is low, the material reaction is incomplete, the proportion of brown corundum generated is small, resulting in material waste. The sintered brown corundum is not treated, the hardness of brown corundum cannot be strengthened, affecting the wear resistance of brown corundum. At the same time, because its production method is to use electric furnace melting and reduction, it consumes a lot of electricity. Faced with the strong pressure of energy conservation and emission reduction, the market urgently needs a new material to replace fused brown corundum. In addition, sintered brown corundum is sintered with high-quality bauxite. At present, the bauxite source is becoming increasingly scarce, and the overall grade of bauxite has declined. It is no longer possible to directly use high-grade ore for calcination. In this way, not only the cost of raw materials increases, but also the aluminum ore resources cannot be used reasonably, resulting in a great waste of high-alumina bauxite resources. Summary of the invention

[0003] 1. Technical issues to be resolved

[0004] In view of the problems existing in the prior art, the present invention provides a method for producing sintered brown corundum to solve the technical problems mentioned in the background technology.

[0005] (II) Technical solution

[0006] To achieve the above object, the present invention provides the following technical solution: a method for producing sintered brown corundum, comprising the following steps:

[0007] Step 1: Material preparation: prepare 45-60 parts of bauxite, 0.3-0.6 parts of carbon material, 30-45 parts of alumina, 60-77 parts of water, 30-45 parts of iron filings, 2-5 parts of carbon fibers, 2-5 parts of raw bauxite ore and 15-23 parts of glaze water by mass, the alumina content in the bauxite is 50-60%, and the length of the carbon fibers is 3-5 cm. Crushing, batching, and grinding: crush the raw bauxite ore into particles, and grind it into fine particles after mixing with sodium carboxymethyl cellulose and boric acid as a binder, and with alumina and water to obtain material A; the mass of the sodium carboxymethyl cellulose is 1-3% of the mass of the raw bauxite ore, the mass of the alumina is 10-35% of the mass of the raw bauxite ore, and the mass of the boric acid is 0.5-3.0% of the mass of the raw bauxite ore;

[0008] Step 2: Material processing: clean the dirt adhered to the alumina during transportation and crush it for later use, crush the carbon material for later use, remove the rust on the outside of the iron filings, crush it for later use, and crush the alumina, carbon material and iron filings to a particle size of 50-150μm after crushing;

[0009] Step 3: Remove iron from material A through an iron remover to obtain material B;

[0010] Step 4: Material mixing: Add the treated alumina, carbon material and iron filings in step 3 to water and mix for 1-3 hours. The mixed materials are filtered and dehydrated to form a mud cake. The mud cake is crushed into crumbs. Glaze water and carbon fiber are added to the crumbs and mixed for 0.8-2.4 hours to form a material mixture.

[0011] Step 5: Blank preparation and drying: The material mixture is extruded into wavy blank mud sheets through a mold, and the blank mud sheets are placed in a drying room for drying. The temperature in the drying room is 60-120°C, and the drying time is 14-26 hours. The air-dried blank mud sheets are cross-stacked in a sintering furnace, and the sintering operation of the sintering furnace is started. The sintering temperature is 1700-2000°C, and the sintering time is 1-3 hours. The blanks are sent to a vertical kiln for firing to obtain sintered brown corundum, and the content of alumina in the sintered brown corundum is 92-97%.

[0012] The present invention is further configured that, in the step 1, grinding is carried out in a wet ball mill, and the mesh number of the material A obtained after grinding is less than or equal to 200 meshes, and the residue on the sieve is less than 5%.

[0013] The present invention is further configured that the step five also includes hardening treatment: timely taking out the brown corundum sintered in the sintering furnace and putting it into the quenching liquid, after quenching, taking out the brown corundum, draining the water, and then piling it in the tempering furnace for tempering; impurity filtering: crushing the produced material, using a magnetic separator to sort the brown corundum in the material for storage and standby.

[0014] The present invention is further configured as follows: in the step five, the thickness of the wavy blank mud sheet is 5-7 cm, the wave height is 20-25 cm, the length of the blank mud sheet is 50-55 cm, the width of the blank mud sheet is 10-15 cm, and holes with a diameter of 5-6 mm are arranged on the outside of the blank mud sheet, and the hole spacing is 5-7 cm.

[0015] The present invention is further configured that the aluminum oxide is α-aluminum oxide and / or γ-aluminum oxide, and the aluminum oxide content is greater than 97%.

[0016] The present invention is further configured such that the stacking height of the blank mud sheets is 1-1.6 m, the stacking width is 1-1.6 m, the stacking length is 1-1.6 m, and the blank mud sheets of adjacent layers are cross-arranged.

[0017] The present invention is further configured such that the volume density of the single block D is 2.25-2.35 g / cm 3 .

[0018] (III) Beneficial effects

[0019] Compared with the prior art, the present invention provides a method for producing sintered brown corundum, which has the following characteristics:

[0020] Beneficial effects:

[0021] The present invention uses high-alumina bauxite ore with loose structure and cannot be directly sintered and industrial alumina or calcined alumina powder as raw materials to produce sintered brown corundum. Compared with the existing fused brown corundum, the produced sintered brown corundum has equivalent aluminum content and good thermal shock stability. It can replace fused brown corundum in many products and achieves good use effect. In addition, the method for producing sintered brown corundum of the present invention removes rust from iron filings by cleaning alumina, reduces impurities inside the sintered brown corundum, improves the adhesion of alumina, carbon materials and iron filings, improves the strength of the sintered brown corundum, and improves the quality of the brown corundum. In addition, by mixing alumina, carbon materials and iron filings into glaze water, the adhesion of the sintered brown corundum is increased, a glaze layer is added to the outer layer of the particles, and the wear resistance of the sintered brown corundum is improved, which is beneficial to the service life of the brown corundum. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The overall flow chart of a method for producing sintered brown corundum in the present invention; DETAILED DESCRIPTION

[0023] Embodiment 1:

[0024] like Figure 1 As shown, the present invention discloses a method for producing sintered brown corundum, comprising the following steps:

[0025] Step 1: Material preparation: prepare 60 parts of bauxite, 0.6 parts of carbon material, 45 parts of alumina, 77 parts of water, 45 parts of iron filings, 5 parts of carbon fiber, 5 parts of raw bauxite ore and 23 parts of glaze water by mass, the alumina content in the bauxite is 60%, and the length of the carbon fiber is 5 cm. Crushing, batching, and grinding: crush the raw bauxite ore into particles, mix with sodium carboxymethyl cellulose and boric acid as binders, and grind into fine particles with alumina and water to obtain material A; the mass of the sodium carboxymethyl cellulose is 3% of the mass of the raw bauxite ore, the mass of the alumina is 35% of the mass of the raw bauxite ore, and the mass of the boric acid is 3.0% of the mass of the raw bauxite ore;

[0026] Step 2: Material processing: clean the dirt adhered to the alumina during transportation and crush it for later use, crush the carbon material for later use, remove the rust on the outside of the iron filings, crush it for later use, and crush the alumina, carbon material and iron filings to a particle size of 150μm after crushing;

[0027] Step 3: Remove iron from material A through an iron remover to obtain material B;

[0028] Step 4: Material mixing: Add the treated alumina, carbon material and iron filings in step 3 into water and mix for 3 hours. The mixed material is filtered and dehydrated to form a mud cake. The mud cake is crushed into crumbs. Glaze water and carbon fiber are added to the crumbs and mixed for 2.4 hours to form a material mixture.

[0029] Step 5: Blank preparation and drying: The material mixture is extruded into wavy blank mud sheets through a mold, and the blank mud sheets are placed in a drying room for drying. The temperature in the drying room is 120°C and the drying time is 26 hours. The air-dried blank mud sheets are cross-stacked in a sintering furnace, and the sintering operation of the sintering furnace is started. The sintering temperature is 2000°C and the sintering time is 3 hours. The blanks are sent to a vertical kiln for firing to obtain sintered brown corundum, in which the content of alumina is 97%.

[0030] In a further embodiment of the present invention, in the step 1, grinding is performed in a wet ball mill, and the mesh size of the material A obtained after grinding is less than or equal to 200 meshes, and the residue on sieve is less than 5%.

[0031] In a further embodiment of the present invention, step five also includes hardening treatment: timely taking out the brown corundum sintered in the sintering furnace and putting it into the quenching liquid, after quenching, taking out the brown corundum, draining the water and piling it into the tempering furnace for tempering; impurity filtration: crushing the produced material, using a magnetic separator to sort the brown corundum in the material for storage and standby.

[0032] In a further embodiment of the present invention, the thickness of the wavy blank mud sheet in step five is 7 cm, the wave height is 25 cm, the length of the blank mud sheet is 55 cm, the width of the blank mud sheet is 15 cm, and holes with a diameter of 6 mm are arranged on the outside of the blank mud sheet, and the hole spacing is 7 cm.

[0033] Embodiment 2:

[0034] A method for producing sintered brown corundum comprises the following steps:

[0035] Step 1: Material preparation: prepare 45 parts of bauxite, 0.3 parts of carbon material, 30-45 parts of alumina, 60 parts of water, 30 parts of iron filings, 2 parts of carbon fiber, 2 parts of bauxite raw ore and 15 parts of glaze water by mass, the alumina content in the bauxite is 50%, and the length of the carbon fiber is 3 cm. Crushing, batching, and grinding: crush the bauxite raw ore into particles, mix with sodium carboxymethyl cellulose and boric acid as binders, and grind into fine particles with alumina and water to obtain material A; the mass of the sodium carboxymethyl cellulose is 1% of the mass of the bauxite raw ore, the mass of the alumina is 10% of the mass of the bauxite raw ore, and the mass of the boric acid is 0.5% of the mass of the bauxite raw ore;

[0036] Step 2: Material processing: clean the dirt adhered to the alumina during transportation and crush it for later use, crush the carbon material for later use, remove the rust on the outside of the iron filings and crush it for later use. The particle size of the alumina, carbon material and iron filings after crushing is 50μm;

[0037] Step 3: Remove iron from material A through an iron remover to obtain material B;

[0038] Step 4: Material mixing: Add the treated alumina, carbon material and iron filings in step 3 to water and mix for 1-3 hours. The mixed materials are filtered and dehydrated to form a mud cake. The mud cake is crushed into crumbs. Glaze water and carbon fiber are added to the crumbs and mixed for 0.8 hours to form a material mixture.

[0039] Step 5: Blank preparation and drying: The material mixture is extruded into wavy blank mud sheets through a mold, and the blank mud sheets are placed in a drying room for drying. The temperature in the drying room is 60°C and the drying time is 14 hours. The air-dried blank mud sheets are cross-stacked in a sintering furnace, and the sintering operation of the sintering furnace is started. The sintering temperature is 1700°C and the sintering time is 1 hour. The blanks are sent to a vertical kiln for firing to obtain sintered brown corundum, in which the content of alumina is 92%.

[0040] In a further embodiment of the present invention, the alumina is α-alumina and / or γ-alumina, and the alumina content is greater than 97%; the stacking height of the blank mud sheet is 1.6m, the stacking width is 1.6m, the stacking length is 1.6m, and the blank mud sheets of adjacent layers are arranged crosswise; the volume density of the single blank D is 2.35g / cm 3 .

[0041] Embodiment 3:

[0042] Embodiment 2:

[0043] A method for producing sintered brown corundum comprises the following steps:

[0044] Step 1: Material preparation: prepare 50 parts of bauxite, 0.4 parts of carbon material, 30-45 parts of alumina, 65 parts of water, 40 parts of iron filings, 4 parts of carbon fibers, 3 parts of raw bauxite ore and 20 parts of glaze water by mass, the alumina content in the bauxite is 55%, and the length of the carbon fibers is 4 cm. Crushing, batching, and grinding: crush the raw bauxite ore into particles, and mix with sodium carboxymethyl cellulose and boric acid as binders, and grind into fine particles with alumina and water to obtain material A; the mass of the sodium carboxymethyl cellulose is 2% of the mass of the raw bauxite ore, the mass of the alumina is 20% of the mass of the raw bauxite ore, and the mass of the boric acid is 2.5% of the mass of the raw bauxite ore;

[0045] Step 2: Material processing: clean the dirt adhered to the alumina during transportation and crush and grind it for later use; crush and grind the carbon material for later use; remove the rust on the outside of the iron filings and crush and grind them for later use; the particle size of the alumina, carbon material and iron filings after crushing is 100μm;

[0046] Step 3: Remove iron from material A through an iron remover to obtain material B;

[0047] Step 4: Material mixing: Add the treated alumina, carbon material and iron filings in step 3 into water and mix for 1 hour. The mixed material is filtered and dehydrated to form a mud cake. The mud cake is crushed into crumbs. Glaze water and carbon fiber are added to the crumbs and mixed for 2.0 hours to form a material mixture.

[0048] Step 5: Blank preparation and drying: The material mixture is extruded into wavy blank mud sheets through a mold, and the blank mud sheets are placed in a drying room for drying. The temperature in the drying room is 100°C and the drying time is 20 hours. The air-dried blank mud sheets are cross-stacked in a sintering furnace, and the sintering operation of the sintering furnace is started. The sintering temperature is 1800°C and the sintering time is 2 hours. The blanks are sent to a vertical kiln for firing to obtain sintered brown corundum, in which the content of alumina is 95%.

[0049] In a further embodiment of the present invention, the alumina is α-alumina and / or γ-alumina, and the alumina content is greater than 97%; the stacking height of the blank mud sheet is 1m, the stacking width is 1m, the stacking length is 1m, and the blank mud sheets of adjacent layers are arranged crosswise; the volume density of the single blank D is 2.25g / cm 3 .

[0050] It should be noted that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, and these modifications and improvements all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for producing sintered brown corundum, characterized in that: The following steps are involved: Step 1: Material preparation: prepare 45-60 parts of bauxite, 0.3-0.6 parts of carbon material, 30-45 parts of alumina, 60-77 parts of water, 30-45 parts of iron filings, 2-5 parts of carbon fibers, 2-5 parts of raw bauxite ore and 15-23 parts of glaze water by mass, the alumina content in the bauxite is 50-60%, and the length of the carbon fibers is 3-5 cm. Crushing, batching, and grinding: crush the raw bauxite ore into particles, and grind it into fine particles after mixing with sodium carboxymethyl cellulose and boric acid as a binder, and with alumina and water to obtain material A; the mass of the sodium carboxymethyl cellulose is 1-3% of the mass of the raw bauxite ore, the mass of the alumina is 10-35% of the mass of the raw bauxite ore, and the mass of the boric acid is 0.5-3.0% of the mass of the raw bauxite ore; Step 2: Material processing: clean the dirt adhered to the alumina during transportation and crush it for later use, crush the carbon material for later use, remove the rust on the outside of the iron filings, crush it for later use, and crush the alumina, carbon material and iron filings to a particle size of 50-150μm after crushing; Step 3: Remove iron from material A through an iron remover to obtain material B; Step 4: Material mixing: Add the treated alumina, carbon material and iron filings in step 3 to water and mix for 1-3 hours. The mixed materials are filtered and dehydrated to form a mud cake. The mud cake is crushed into crumbs. Glaze water and carbon fiber are added to the crumbs and mixed for 0.8-2.4 hours to form a material mixture. Step 5: Blank preparation and drying: The material mixture is extruded into wavy blank mud sheets through a mold, and the blank mud sheets are placed in a drying room for drying. The temperature in the drying room is 60-120°C, and the drying time is 14-26 hours. The air-dried blank mud sheets are cross-stacked in a sintering furnace, and the sintering operation of the sintering furnace is started. The sintering temperature is 1700-2000°C, and the sintering time is 1-3 hours. The blanks are sent to a vertical kiln for firing to obtain sintered brown corundum, and the content of alumina in the sintered brown corundum is 92-97%.

2. A method for producing sintered brown corundum according to claim 1, characterized in that: In the step 1, grinding is performed in a wet ball mill, and the mesh size of the material A obtained after grinding is less than or equal to 200 meshes, and the sieve residue is less than 5%.

3. A method for producing sintered brown corundum according to claim 1, characterized in that: The step five also includes hardening treatment: timely taking out the brown corundum sintered in the sintering furnace and putting it into the quenching liquid, taking out the brown corundum after quenching, draining the water and piling it into the tempering furnace for tempering; impurity filtering: crushing the produced material, using a magnetic separator to sort the brown corundum in the material for storage and standby.

4. A method for producing sintered brown corundum according to claim 1, characterized in that: In the step 5, the thickness of the wavy blank mud sheet is 5-7 cm, the wave height is 20-25 cm, the length of the blank mud sheet is 50-55 cm, the width of the blank mud sheet is 10-15 cm, and holes with a diameter of 5-6 mm are arranged on the outside of the blank mud sheet, and the hole spacing is 5-7 cm.

5. A method for producing sintered brown corundum according to claim 1, characterized in that: The aluminum oxide is α-aluminum oxide and / or γ-aluminum oxide, and the aluminum oxide content is greater than 97%.

6. A method for producing sintered brown corundum according to claim 5, characterized in that: The stacking height of the blank mud sheets is 1-1.6 m, the stacking width is 1-1.6 m, the stacking length is 1-1.6 m, and the blank mud sheets of adjacent layers are cross-arranged.

7. A method for producing sintered brown corundum according to claim 6, characterized in that: The bulk density of the single block D is 2.25-2.35 g / cm 3 .

Citation Information

Cited By

  • Production method of brown aluminum oxide

    CN121021130A